Experimental Study of Utilization Corn Weevil Ash Against Concrete Strength - Putri, Fela Hanifa; Melinda, Annisa Prita; Putri, Prima Yane (Universitas Negeri Padang, 2023)
Concrete making that continues to develop rapidly requires quite a lot of materials, this leads to a decrease in natural resources available for concrete making purposes, so that the search for alternative materials as substitutes and added materials from other natural resources or artificial resources. One of the alternative added ingredients to be used is corn weevil. The purpose of this study was to determine the effect of corn weevil ash on compressive strength, bending strength and shear strength of concrete. The method used is an experimental method in quantitative data. The test objects made totaled 36 pieces with 12 cylinders measuring 15 x 30 cm and 24 blocks measuring 15 x 15 x 53 cm. With the results of the compressive strength test, it decreased along with the increase in the percentage of ABJ 0%, 5%, 10% and 15%, namely 24.08 MPa, 23.21 MPa, 20.22 MPa, 14.70 MPa. For strong bending results, there was an increase in the addition of ABJ 0%, 5% and 15%, namely 1.45 MPa, 1.65 MPa, 1.54 MPa, 1.56 MPa. And in the shear strength test, there was a maximum increase in the addition of a 10% ABJ percentage, which was 20.05 kN and a decrease in the addition of ABJ by 5% and 15%, namely 18.75 kN and 18 kN while for normal concrete it was 19.27 kN.